Perceptions about switchgrass and land allocation decisions: Evidence from a farmer survey in Missouri. (October 2021) - Burli, Pralhad; Lal, Pankaj; Wolde, Bernabas; Jose, Shibu; Bardhan, Sougata
Abstract: Switchgrass has been identified as a high potential bioenergy feedstock, and was expected to play an important role in achieving the production targets for cellulosic biofuels laid out under the Energy Security and Independence Act of 2007. However, the development of cellulosic biofuels at commercially viable levels has been slower than anticipated and supply side challenges, due to limited feedstock availability, continue to be a major bottleneck. Understanding the role of the farming community, their perceptions, and their willingness to cultivate dedicated bioenergy feedstocks is an important part of overcoming these challenges. To this end, a survey was administered in March-April 2017 and the results of our analysis are both insightful and timely. We studied the role of farmer perceptions around the suitability of switchgrass for their operations. We evaluated the impact of their perceptions and existing land uses on their willingness to cultivate switchgrass and their land allocation decisions using a 2-step Heckman model. Factors such as potential for diversification of crop-mix, creation of habitat for wildlife, as well as ownership of woodland or forestland played an important role in influencing farmer willingness to cultivate switchgrass. We also found that land allocated for switchgrass cultivation was more likely to come from lands under non-crop uses, such as hay or other land use, and was unlikely to cause displacement of lands used for cultivating row crops, which obviates conflicts that could arise from competing land use vis-à-vis food-crops. Highlights: Holdings in woodland positively influence willingness to cultivate switchgrass. Crop diversification potential increases willingness to cultivate switchgrass. Farmer willingness is higher when they can create a habitat for wildlife. Land allocated for switchgrass is more likely to come from non row-crop uses.